THE THEOLINGUISTIC ANALYSIS OF AL-FARABI’S «KITAB MAQALAT AR-RAFI’A FI USUL AT-TABI’A» (BASED ON THE «NAFS» SECTION) (Journal of Oriental Studies, 2026)
This article offers a theolinguistic analysis of the third section, “Nafs”, from al-Farabi’s Kitab Maqalat ar-Rafi‘a fi Usul at-Tabi‘a. The study focuses on examining and interpreting al-Farabi’s understanding of ruh (spirit), ‘aql (intellect), and nafs (soul) within the framework of Qur’anic verses, prophetic hadiths, and classical Islamic scholarly traditions. The introduction outlines the main directions of al-Farabi studies in the fields of religious studies, Islamic studies, and Oriental studies in Kazakhstan since the country gained independence.The primary objective of the research is to conduct a theolinguistic examination of al-Farabi’s philosophical and religious explanations of nafs, comparing his views with those of classical Muslim scholars and prominent Kazakh thinkers such as Abai and Shakarim. The main focus of the article is to clarify the semantic field of the term nafs, identify its linguistic nuances in both Arabic and Kazakh, and determine the Islamic foundations underlying al-Farabi’s interpretation through Qur’anic and prophetic sources. The scientific and practical significance of the study lies in revealing the intersection between theolinguistics and Islamic philosophy in al-Farabi’s treatises by interpreting his theological and philosophical ideas through linguistic and hermeneutic approaches. The methodology includes descriptive, comparative, generalization, specification, hermeneutic, and synchronic–diachronic methods.The findings demonstrate that al-Farabi conceptualized nafs as a non-material yet vital energetic force that connects the body and the soul. In addition, his interpretation of Ruh al-Qudus differs from that of mainstream Qur’anic exegetes, reflecting a distinctive philosophical position within his theological framework. The study also identifies a semantic narrowing of the concept nafs in the Kazakh language compared to its broader Arabic meanings.In conclusion, the article emphasizes the importance of integrating theological and Arabic linguistic perspectives in the study of al-Farabi’s works and proposes a comprehensive model for the theolinguistic analysis of medieval Islamic philosophical texts.Keywords: al-Farabi, Arabic, religion, nafs (soul), theolinguistics, spirit, Islamic philosophy.